Biomedical and Health Informatics Research and Education at the University of Washington - Fuller, S.; Kalet, I.; Tarczy-Hornoch, P. (Yearbook of Medical Informatics, 2000)
Although an extensive medical informatics research program as well as courses and training experiences in biomedical informatics have existed at the University of Washington (UW) for many years, a formal home did not exist until 1997 when the Division of Biomedical Informatics was created in the Department of Medical Education, School of Medicine. Since that time the expansion of the research, service and teaching programs has been rapid with a key milestone being a university commitment to provide funding, space and faculty to support the development of a new graduate program in Biomedical and Health Informatics.Hallmarks of the biomedical and health informatics program at the University of Washington include:- Strong shared belief that informatics research can contribute to the improvement of healthcare and health;- Large, multidisciplinary faculty including faculty from computer science, library and information science as well as the health sciences schools (dentistry, medicine, nursing, pharmacy, and public health and community medicine);- Comprehensive research and development partnership with the University of Washington Medical Centers information systems group and the UW Primary Care Network to move research from the laboratory to operational clinical systems;- Extensive and diverse regional setting in which to study information needs and develop informatics solutions in primary care settings;- Lack of barriers to interdisciplinary research and teaching.